Design, simulations, and optimizations of mid-infrared multiple quantum well LEDs - Ding, Ying (2018)
We use eight-band k·p energy band structure model to help design novel GaInSb/AlGaInSb mid-infrared multiple quantum well (MQW) structures with an emitting mid-infrared waveband of 4-5 μm. Simulation results suggest that the number of quantum wells has little influence on the spontaneous emission rate and gain because of no strong coupling between quantum wells and they just simply follow scaling laws. The SiLENSe software module from STR-soft is used to investigate injection efficiency of the designed MQW structures. Simulation results indicate that the MQW structures offer better carrier confinement i.e. higher carrier injection efficiency compared with traditional bulk active regions which are currently used for mid-infrared LEDs and sensors. Experimental investigations show that the MQW LEDs with a seven wells structure show an increase of a factor 2 in wall plug efficiency and output power compared with conventional bulk LEDs at the same wavelength.